Comparing Underlying and Contributory Cause of Death in Registry Data With End-of-Life Proxy Interviews: Findings From The Irish Longitudinal Study on Ageing (TILDA). (October 2021) - Ward, Mark; May, Peter; Normand, Charles; Kenny, Rose Anne; Nolan, Anne
Cause of death is an important outcome in end-of-life (EOL) research. However, difficulties in assigning cause of death have been well documented. We compared causes of death in national death registrations with those reported in EOL interviews. Data were from The Irish Longitudinal Study on Ageing (TILDA), a nationally representative sample of community-dwelling adults aged 50 years and older. The kappa agreement statistic was estimated to assess the level of agreement between two methods: cause of death reported in EOL interviews and those recorded in official death registrations. There was moderate agreement between underlying cause of death recorded on death certificates and those reported in EOL interviews. Discrepancies in reporting in EOL interviews were systematic with better agreement found among younger decedents and where the EOL informant was the decedents' partner/spouse. We have shown that EOL interviews may have limited utility if the main goal is to understand the predictors and antecedents of different causes of death.